2009
DOI: 10.1073/pnas.0900060106
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin regulates root meristem activity via modulation of the polar auxin transport

Abstract: Plant development is governed by signaling molecules called phytohormones. Typically, in certain developmental processes more than 1 hormone is implicated and, thus, coordination of their overlapping activities is crucial for correct plant development. However, molecular mechanisms underlying the hormonal crosstalk are only poorly understood. Multiple hormones including cytokinin and auxin have been implicated in the regulation of root development. Here we dissect the roles of cytokinin in modulating growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
274
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(307 citation statements)
references
References 45 publications
26
274
2
1
Order By: Relevance
“…4a,b). This phenotype is also consistent with perturbation of cytokinin status, as increase in cytokinin levels normally inhibit root growth and reduce the size of root meristems [22][23][24] . Thus, we speculated that disrupting AtABCG14 may impair root meristem activity.…”
Section: Disruption Of Atabcg14 Causes Cytokinin-deficient Phenotypessupporting
confidence: 73%
“…4a,b). This phenotype is also consistent with perturbation of cytokinin status, as increase in cytokinin levels normally inhibit root growth and reduce the size of root meristems [22][23][24] . Thus, we speculated that disrupting AtABCG14 may impair root meristem activity.…”
Section: Disruption Of Atabcg14 Causes Cytokinin-deficient Phenotypessupporting
confidence: 73%
“…In the cre1 mutant, rhizobia are unable to inhibit acropetal auxin transport and this is associated with a misregulation of some PIN auxin carrier-encoding gene expression and protein accumulation (Plet et al, 2011). The hypothesis that cytokinin acts upstream of auxin transport regulation is supported by studies from Arabidopsis showing that cytokinin regulates PIN expression, accumulation, selective degradation, and subsequently polar auxin transport (Pernisová et al, 2009;Ruzicka et al, 2009;Marhavý et al, 2011Marhavý et al, , 2014. This is thought to regulate auxin accumulation during lateral root formation (Laplaze et al, 2007;Marhavý et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed our results showed that an increasing Figure S5). Therefore, cytokinin regulation of the fundamental cellular process (cell morphogensis) appears to follow the common theme for the coordination of various developmental and morphogenetic processes in different tissues/organs involving a balancing act between cytokinin and auxin, although detailed mechanisms for the auxin-cytokinin balancing act may differ in different processes [1,5,6,[8][9][10][11]42]. How does cytokinin antagonize the action of auxin in PC morphogenesis?…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, cytokinin is known to promote cell division, stem-cell specification, and chloroplast biogenesis [9][10][11][12]. The major cytokinin biosynthetic pathway is mediated by adenosine phosphate-isopentenyltransferase (IPT), which catalyzes the first and rate-limiting step [13,14].…”
Section: Introductionmentioning
confidence: 99%